Expression of mitochondrial dysfunction-related genes and pathways in paclitaxel-induced peripheral neuropathy in breast cancer survivors. Issue 1 (December 2018) - Kober, Kord M; Olshen, Adam; Conley, Yvettte P; Schumacher, Mark; Topp, Kimberly; Smoot, Betty; Mazor, Melissa; Chesney, Margaret; Hammer, Marilyn; Paul, Steven M; Levine, Jon D; Miaskowski, Christine
Background: Paclitaxel is one of the most commonly used drugs to treat breast cancer. Its major dose-limiting toxicity is paclitaxel-induced peripheral neuropathy (PIPN). PIPN persists into survivorship and has a negative impact on patient's mood, functional status, and quality of life. No interventions are available to treat PIPN. A critical barrier to the development of efficacious interventions is the lack of understanding of the mechanisms that underlie PIPN. Mitochondrial dysfunction has been evaluated in preclinical studies as a hypothesized mechanism for PIPN, but clinical data to support this hypothesis are limited. The purpose of this pilot study was to evaluate for differential gene expression and perturbed pathways between breast cancer survivors with and without PIPN. Methods: Gene expression in peripheral blood was assayed using RNA-seq. Differentially expressed genes (DEG) and pathways associated with mitochondrial dysfunction were identified between survivors who received paclitaxel and did (n = 25) and did not (n = 25) develop PIPN. Results: Breast cancer survivors with PIPN were significantly older; more likely to be unemployed; reported lower alcohol use; had a higher body mass index and poorer functional status; and had a higher number of lower extremity sites with loss of light touch, cold, and pain sensations and higher vibration thresholds. No between-group differences were found in the cumulative dose of paclitaxel received or in the percentage of patients who had a dose reduction or delay due to PIPN. Five DEGs and nine perturbed pathways were associated with mitochondrial dysfunction related to oxidative stress, iron homeostasis, mitochondrial fission, apoptosis, and autophagy. Conclusions: This study is the first to provide molecular evidence that a number of mitochondrial dysfunction mechanisms identified in preclinical models of various types of neuropathic pain including chemotherapy-induced peripheral neuropathy are found in breast cancer survivors with persistent PIPN and suggest genes for validation and as potential therapeutic targets.